Biofortification of Food Crops - Singh, Ummed; Praharaj, C S.; Singh, S S.; Singh, N P. (Springer India : Imprint: Springer, 2016)
The chapters presented in this book 'Biofortification of Food Crops' depict how agricultural technological interventions have true role in alleviating malnutrition. This book highlights the role of multidisciplinary approaches to cope up with the challenges of micronutrient malnutrition or hidden hunger which is an alarming public health issue in most parts of the world including India. In this endeavour, different biofortification approaches such as agronomic (or ferti-fortification), breeding, biotechnological, physiological, microbial etc. has fulfilled their different mandates of nutrient enrichment of food crops including cereals and pulses. The contents of the book proves that biofortified plants have adequate potential to nourish nutrient depleted soils, help increase crop productivity and provide nutritional benefits to plants, humans and livestock. The content and quality of information presented in this book will definitely provide multiple novel ideas of advance techniques and will stimulate innovative thoughts and directions amongst researchers and policy makers in the field of biofortification. In addition, the contributions presented in the book will be a good source of background knowledge and technical know-how to educate the readers about biofortification. The authors hope that the book entitled "Biofortification of Food Crops" would provide a suitable platform in our collective efforts for an appropriate dialogue among the scientists, researchers, entrepreneurs, policy makers and farmers in reducing the budding issues of malnutrition through novel approaches and means.